Psychometric network analysis reveals how sensory processing relates to self-reflection traits in adolescence - Lisa Raoul; Marie-Hélène Grosbras (PLoS ONE, 2025)
While recent research links sensory processing to mental traits, this has scarcely been explored in adolescence, a period characterized by changes in self-reflection and onset of mental disorders. This study aims to fill this gap using psychometric network analyses to examine how sensory processing characteristics (somatosensation and interoception) relate to self-reflection traits (tendency to examine one’s body, thoughts, and one’s relation to others) in youths aged 10–25 (N = 816) and whether these associations change with sex and age. Results revealed an interconnected network of sensory and self-reflection variables, organized around three main communities. A first showed that elevated social anxiety is associated with heightened sensitivity to somatosensation; a second that positive reflection towards body appearance positively relate to confidence in interoceptive sensations; a third that reflection towards one’s thoughts (private self-consciousness) linked interoceptive awareness with reflection related to others’ thoughts. Some of these associations between sensory and self-reflection traits are stronger in girls and late adolescence, but results regarding age effects were inconsistent. These findings highlight the need to integrate sensorial aspects into our understanding of adolescents’ psychology.